2015
DOI: 10.3389/fnins.2014.00436
|View full text |Cite
|
Sign up to set email alerts
|

Sensory synergy as environmental input integration

Abstract: The development of a method to feed proper environmental inputs back to the central nervous system (CNS) remains one of the challenges in achieving natural movement when part of the body is replaced with an artificial device. Muscle synergies are widely accepted as a biologically plausible interpretation of the neural dynamics between the CNS and the muscular system. Yet the sensorineural dynamics of environmental feedback to the CNS has not been investigated in detail. In this study, we address this issue by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Consequently, activated motor commands of the prosthesis enable intuitive motor control by the wearer and simultaneous confirmation with visual feedback. In short, the output of sensory synergy is used as an input to both the CNS and the TLS, and control signals for the prosthesis device are created through motor synergy that combines signals from the CNS and the prosthesis device (Alnajjar et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, activated motor commands of the prosthesis enable intuitive motor control by the wearer and simultaneous confirmation with visual feedback. In short, the output of sensory synergy is used as an input to both the CNS and the TLS, and control signals for the prosthesis device are created through motor synergy that combines signals from the CNS and the prosthesis device (Alnajjar et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Recently, a few studies have reported increased sensory information density by neural implants (Ciancio et al, 2016); however, neurophysiological studies have indicated that position in space is estimated by integrating information from multiple sensory inputs rather than direct input. Moreover, as this integrated feedback is noise-robust, useful and cost-effective, adding appropriate sensory integration may result in better reconstruction (Alnajjar et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Tacit Learning System (TLS; Shimoda and Kimura, 2010;Shimoda et al, 2013) is a closed-loop control system that allows adaptive movement in response to unexpected environmental changes. In its function, it contributes to a strategy of sensory feedback called sensory synergy (Alnajjar et al, 2015). The TLS is superior to conventional methods in terms of learning speed, cost, and robustness.…”
Section: Introductionmentioning
confidence: 99%
“…These circuits promote the generation of necessary neural patterns for organized movement (4)(5)(6). In addition, Llinas and Roy (7) have suggested that organized movement is generated internally without the need for sensory input.…”
Section: Introductionmentioning
confidence: 99%